Parasitic leiomyoma causing small bowel perforation: A case report - Anya Laibangyang; Cassandra Law; Gunjan Gupta; Xiang Da Dong; Linus Chuang (Elsevier, 2021)
Background: Parasitic leiomyomas are rare extra-uterine tumors that can be seen in patients after myomectomy or morcellation of leiomyomas. Case: A 63-year-old woman with a history of abdominal myomectomy 20 years prior presented with worsening abdominal distension and pain for the past eight months. The patient delayed care due to fear of the COVID-19 pandemic and was found to have a 42 cm parasitic leiomyoma attached to the small bowel causing obstruction and perforation. Conclusion: Parasitic leiomyomas can cause small bowel obstruction and perforation.